Материалы к фауне пядениц рода Eupithecia (Lepidoptera, Geometridae) Крыма с описанием нового вида - Миронов, В.Г. (Вестник зоологии, 1988)
32 species of the genus Eupithecia are established for the Crimea. 20 of them are recorded for the first time. E. karadaghensis sp. n. (type-locality: Crimea, Karadagh) is similar to E. egenaria H.-S. and E. pimpinellata H b., differs from both in external morphology and genitalia structure of males and females. Type-material is deposited in the Zoological Institute, USSR Academy of Sciences (Leningrad).